THE RELATION OF PHYSICAL WORKLOAD AND QUALITY OF SLEEP WITH FATIGUE OF CONSTRUCTION WORKER IN PT. X CITY OF SEMARANG - Virgi Hesti Anggorokasih; Baju Widjasena; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Construction workers are working use more physical strength so it results high physical workload. If the physical workload of workers increases, then workers will feel fatigue quickly. In addition, excessive work time causes the worker's rest and sleep time to be reduced and results in decreased stamina. This study aimed to analyze the relationship between physical workload and sleep quality with work fatigue in construction workers at PT. X City of Semarang. This research was a quantitative study with cross sectional design. The population of the study were 174 respondents. The sample were 52 workers at PT. X City of Semarang. This study used a pulse oxymeter to measure physical workload and a Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality of workers. Moreover, the Deary Liewald Reaction Time Tester was used to measure the level of work fatigue. The result showed that there is no relationship of physical workload (p-value = 0.326) with work fatigue and there is a relationship between sleep quality (p-value = 0.020) with work fatigue. Researcher suggest to improve existing dwellings, supervise hygiene and environmental sanitation of dwellings and do regular stretching at work.